Nutrient patterns and non-alcoholic fatty liver disease in Iranian Adul: A case-control study - Ammar Salehi-sahlabadi; Farshad Teymoori; Farshad Teymoori; Hamid Ahmadirad; Ebrahim Mokhtari; Mina Azadi; Shaikh Sanjid Seraj; Azita Hekmatdoost (Frontiers in Nutrition, 2022)
BackgroundsThe current literature boasts the importance of diet in preventing or managing liver complications. However, there is limited evidence on the association of nutrient patterns (NP) with these complications. In this case-control study, we aimed to examine the possible relationship between nutrient patterns and the risk of non-alcoholic fatty liver disease (NAFLD) amongst the adult Iranian population.MethodsThis case-control study is being conducted at the Metabolic Liver Disease Research Center at Isfahan University of Medical Sciences in 2019. The study included 225 newly diagnosed cases of NAFLD and 450 controls. A validated semi-quantitative food frequency questionnaire (FFQ) assessed dietary intake. Principal component analysis using Varimax rotation obtained nutrient patterns. Logistic regression was performed to estimate NAFLD risk.ResultsWe identified four major nutrient patterns. The first nutrient pattern was high in consumption of lactose, animal protein, vitamin D, riboflavin, pantothenic acid, vitamin B12, calcium, phosphorus, zinc, and potassium. The second nutrient pattern included fiber, plant protein, vitamin A, thiamine, niacin, copper, and selenium, while the third featured plant protein, zinc, copper, magnesium, manganese, chromium, and selenium. The fourth was characterized by fructose, vitamin A, pyridoxine, vitamin C, and potassium. After adjusting for confounders, individuals in the highest tertile of NP4 had lower odds of NAFLD (OR: 0.56, 95% CI: 0.32–0.98, P_trend = 0.042); compared to those who were in the lowest tertile.ConclusionHigh compliance to a nutrient pattern characterized by fructose, vitamin C, vitamin A, pyridoxine, and potassium mainly supplied from fruits, vegetables, and nuts is inversely proportional to the odds of NAFLD. Also our findings indicate a very high fiber intake, a relatively optimal dietary fat profile, and a pretty low sugar intake for cases and controls, unseen in western countries. However, these initial findings need to be approved with further studies to confirm the relationship between nutrient patterns and NAFLD.